2010
DOI: 10.1677/joe-09-0431
|View full text |Cite
|
Sign up to set email alerts
|

The GH/IGF1 axis and signaling pathways in the muscle and bone: mechanisms underlying age-related skeletal muscle wasting and osteoporosis

Abstract: The widespread increase in life expectancy is accompanied by an increased prevalence of features of physical frailty. Signs and symptoms may include sarcopenia and osteopenia, reduced exercise capacity, and diminished sense of wellbeing. The pathogenesis of age-associated sarcopenia and osteopenia is multifactorial, and hormonal decline may be a contributing factor. Aging is associated with a progressive decrease in GH secretion, and more than 30% of elderly people have circulating IGF1 levels below the normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
197
0
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(220 citation statements)
references
References 107 publications
(84 reference statements)
10
197
0
13
Order By: Relevance
“…The growth hormone/IGF-1 axis has been widely examined as a potential mediator of skeletal muscle loss (Perrini et al 2010;Harridge 2003;Scicchitano et al 2009). In a recent application of the EWGSOP criteria for sarcopenia in community-dwelling older people, IGF-1 in the lowest tertile was associated with approximately fourfold higher odds for sarcopenia, a finding that was initially corroborated in our study (Volpato et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The growth hormone/IGF-1 axis has been widely examined as a potential mediator of skeletal muscle loss (Perrini et al 2010;Harridge 2003;Scicchitano et al 2009). In a recent application of the EWGSOP criteria for sarcopenia in community-dwelling older people, IGF-1 in the lowest tertile was associated with approximately fourfold higher odds for sarcopenia, a finding that was initially corroborated in our study (Volpato et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These pathological states share unique features and are all characterized by a loss of collagen type I, dysregulated fibroblast-matrix interactions and impaired fibroblast interactions with organ parenchyma, mainly with organ-specific epithelial cells and muscle (Wenk et al, 1999(Wenk et al, , 2004Krtolica & Campisi, 2002;Campisi, 2005;Labat-Robert & Robert, 2007;Treiber et al, 2009). A variety of genetic and environmental factors including increased concentration of ROS, mitochondrial dysfunction (Hiona & Leeuwenburgh, 2008), changes in autocrine, paracrine and endocrine release of hormones, growth factors (Perrini et al, 2010) and cytokines (Coppe et al, 2008) have been identified to contribute to skin aging, sarcopenia and osteoporosis in humans and rodents (Zofkova, 2003;Raisz, 2005;Ralston & de Crombrugghe, 2006;Hiona & Leeuwenburgh, 2008;Marzetti et al, 2009). Research on the regulation of connective tissue organization by enhanced release of ROS from mitochondria during fibroblast aging is a matter of increasing interest and relevance as it may provide ultimate clues for mechanisms underlying disruption of connective tissue homoeostasis in aging-related skin atrophy, sarcopenia and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic acidosis potentially accelerates proteolysis and amino acid catabolism, probably through activation of caspase-3 and the ubiquitin proteasome system or via effects on the growth hormone/IGF-1 axis (97,(182)(183)(184)(185)(186) .…”
Section: Dietary Acid-base Loadmentioning
confidence: 99%